2021
DOI: 10.3389/fpsyg.2021.614607
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hyperpalatable Baby Foods and Exposure During Infancy: A Preliminary Investigation

Abstract: Objective: To characterize the prevalence of hyperpalatable foods (HPF) among baby foods in the U.S. and examine the prevalence of HPF exposure and consumption from both baby food and adult food sources among infants aged 9–15 months.Methods: A U.S. baby food database as well as baby foods from three 24-h dietary recalls of 147 infants were used to identify baby foods as HPF per previous publication. HPF exposure was defined as intake of any HPF during the 3-day measurement period. To determine the extent of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Our preliminary work has documented the extensive degree to which infants may be exposed to HPF early in life, indicating that this is a major cause for concern. Among a large sample of infants aged 9–15 months from the United States, our findings revealed that the majority (>90%) of infants were exposed to HPF by 15 months of age 41 . Furthermore, HPF comprised 38%–52% of infants' daily energy intakes from food 41 .…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Our preliminary work has documented the extensive degree to which infants may be exposed to HPF early in life, indicating that this is a major cause for concern. Among a large sample of infants aged 9–15 months from the United States, our findings revealed that the majority (>90%) of infants were exposed to HPF by 15 months of age 41 . Furthermore, HPF comprised 38%–52% of infants' daily energy intakes from food 41 .…”
Section: Introductionmentioning
confidence: 70%
“…Researchers could also consider examining the effects of exposures on the development of food preferences, a key outcome used in exposure‐learning research on dietary health in infancy and early childhood 43 . Researchers may also consider examining outcomes related to overall dietary intake, and intake of HPF, assessed using measures such as a 24‐h dietary recall 44 with procedures adapted to characterize infant dietary intake 41,45 . Dietary recalls provide detailed data on the nutrients of all foods and beverages consumed, which can be used to identify and quantify HPF intake via a standardized quantitative definition 29 .…”
Section: New Paradigm For Investigating the Etiology Of Obesity In Ea...mentioning
confidence: 99%
See 3 more Smart Citations